CORAL REEFS - Terry Indrabudi; Robert Alik (Widyariset, 2017)
Coastal development in Ambon Bay led to increased sedimentation and pollutant into the waters. It  effects on organism in Ambon Bay, including coral reefs. This study aims to look the condition of coral reef. The study method is Line Intercept Transect (LIT) in eight observasion stations, two stations in the inner bay and six stations in the outside bay. The results showed there has been a decline in coral cover in the area that has development activities and high antropogenic activity like Hative Besar, Poka, Kota Jawa, Halong, and Hunuth station. As for areas that have lesser development activity and antropogenic activity, the condition of coral cover increased as happened at Lilibooy, Eri, and Batu Capeu stations. Stations that have coral reefs “very good category” is at St. Eri station, “good category” is at St. Lilibooy station, “medium category” is at St. Kota Jawa station and St. Batu Capeu while “bad category” are at St. Hative Besar, St. Poka, St. Halong and St. Hunuth stations. Coral growth at each station is dominated by a non-acropora group. The life forms are massive corals and submassive corals from Porites, Favites, Platygyra, Millepora, Symphyllia, Lobophyllia, Styphora and Pavona genus.